Long-Lasting T Cell Responses in BNT162b2 COVID-19 mRNA Vaccinees and COVID-19 Convalescent Patients - Hurme, Antti; Jalkanen, Pinja; Heroum, Jemna; Liedes, Oona; Vara, Saimi; Melin, Merit; Teräsjärvi, Johanna; He, Qiushui; Pöysti, Sakari; Hänninen, Arno; Oksi, Jarmo; Vuorinen, Tytti; et al. (Frontiers in Immunology, 2022)
The emergence of novel variants of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has made it more difficult to prevent the virus from spreading despite available vaccines. Reports of breakthrough infections and decreased capacity of antibodies to neutralize variants raise the question whether current vaccines can still protect against COVID-19 disease. We studied the dynamics and persistence of T cell responses using activation induced marker (AIM) assay and Th1 type cytokine production in peripheral blood mononuclear cells obtained from BNT162b2 COVID-19 mRNA vaccinated health care workers and COVID-19 patients. We demonstrate that equally high T cell responses following vaccination and infection persist at least for 6 months against Alpha, Beta, Gamma, and Delta variants despite the decline in antibody levels.